An efficient one-pot two-step three-component process for the synthesis of perfluoroalkylated biphenyls. Issue 5 (4th February 2015) - Xu, Yuhong; Han, Jing; Lv, You; Pan, Renming; Chen, Jie; Deng, Hongmei; Shao, Min; Zhang, Hui; Cao, Weiguo
Abstract: A practical and economical process for the synthesis of perfluoroalkylated biphenyl derivatives has been developed. The three-component reaction of aromatic ketones, malononitrile and methyl perfluoroalk-2-ynoates gave the desired products in good to excellent yields via a one-pot two-step process. Graphical abstract: